Influence of Post-Collision-Interaction in Auto-ionization - L, Henmedekh; O, Lhagva; J, Madsen (Scientific transaction of the National University of Mongolia. Physics, 2022)
Following the ideas of Senashenko we obtain an expression for the resonant part of the auto-ionizing transition matrix consisting of the standart first Born expression, and an additional factor containing the remaining effects of Post-Collision-Interaction. This factor becomes very important when one studies the angular dependence of auto-ionization from spherical symmetric auto-ionization states. We in particular concentrate on decay form the (2s2)1S state since an experimental investigation of this process has recently been published.